Controlled release of herbicide into water from beta-naphtoxyacetic acid-layered double hydroxide nanohybrid formulation - Binti Jubri Z.; Binti Mohd Yusoff N.Z.A.; Binti Marsom E.S.; Binti Sarijo S.H. (2023)
At present, the use of huge quantities of herbicides in conventional agriculture has lead to some major environmental problems. Controlled release formulations (CRF) are now being developed to avoid such problems. The release of beta-naphtoxyacetic acid (BNOA) into aqueous solution from controlled-release formulation (CRF) prepared by the intercalation of BNOA anion into Zn-Al-layered double hydroxide (ZAL) was studied. CRF consisting of organicinorganic nanohybrid material was synthesized by coprecipitation method using BNOA as guest anion and Zn-Al-LDH as the inorganic host. As a results of successful intercalation of BNOA ion into Zn-Al-LDH, the powder X-ray diffractogram shows that the basal spacing of Zn-Al-LDH with BNOA as interlayer ion expanded from 8.93 to 19.46 . This expansion is to accommodate BNOA ion for the formation of Zn-Al-BNOA nanocomposite (ZAB). The reverse process, i.e., the deintercalation or release of the guest, BNOA was found to be rapid initially, followed by more sustained release thereafter and this behavior was dependent on the type of anions and the concentrations of the release medium, the aqueous solution. The mechanism of release has been interpreted on the basis ion-exchange process between the BNOA anion intercalated into the interlamellae host and carbonate or chloride and/or hydroxyl anions in the aqueous solution. 2009 IEEE.